Rituximab for post-transplantation Focal Segmental Glomerulosclerosis (FSGS) relapse: a case report - Saber, Luciana Tanajura Santamaria; Bastos, Camila; Mothé, Ricardo Araújo; Costa, Roberto Silva; Muglia, Valmir Aparecido; Giovannetti, Mariana Arreaza; Lima, Tatiana Silva (Brazilian Journal of Transplantation, 2010)
After a first renal transplantation, 20% to 40% of Focal Segmental Glomerulosclerosis (FSGS) relapse, frequently leading to renal loss. These data can increase in more than 80% of patients receiving a second transplant after a recurrence. Although often ineffective, plasmapheresis is still considered to be the first option to treat relapses. Recently, anti-CD-20 monoclonal antibody Rituximab (RTX) has appeared as an alternative choice. We report a case of a 34 year old male patient who was submitted to a kidney transplant from deceased donor due to end stage renal disease secondary to a non-biopsied glomerulonephritis. About 40 days after transplant he presented nephrotic syndrome, diagnosed as FSGS. He underwent five plasmapheresis sessions with no response. Then, he received two intravenous doses of RTX 375mg/m2, with a seven day interval between doses and a third dose 60 days after the second one. This strategy allowed attaining sustained full remission of the nephrotic syndrome and excellent graft function, which persists one year after RTX treatment.